Analisis Fungsi Retoris al-Jinās terhadap Akurasi Makna dalam Terjemahan al-Qur’an Bahasa Indonesia: Studi pada Ayat-Ayat Juz ‘Amma - Zainuddin Mansur Munir (ALSYS, 2026)
Studies on Qur’an translation are not only concerned with the transfer of lexical meaning but also with the preservation of rhetorical functions that shape the aesthetic and semantic power of the source text. This study aimed to identify verses in Juz ‘Amma that contain al-jinās, analyze their rhetorical functions in the Arabic text, and evaluate their influence on semantic accuracy in Indonesian translations of the Qur’an. This study used a descriptive qualitative approach with content analysis and critical discourse analysis methods. The research data consisted of Qur’anic verses in Juz ‘Amma and three Indonesian translation versions, namely the Translation of the Ministry of Religious Affairs of the Republic of Indonesia (2019), Tafsir Al-Mishbah by M. Quraish Shihab, and Al-Muntakhab by the Indonesian Ulema Council. The results showed that the occurrence of al-jinās was uneven and dominated by the form of jinās nāqiṣ, which often intersected with other rhetorical devices such as saj‘ and takrār. This pattern indicates that the aesthetic construction of short surahs relies more on sound harmony and rhythm than on identical lexical similarity. In translation, the basic meaning is generally maintained; however, the rhetorical function of al-jinās cannot always be preserved consistently because of phonological differences between Arabic and Indonesian. As a result, aesthetic and stylistic effects tend to be reduced, so that some meaning relations originally reinforced by sound patterns in the source text are not fully conveyed. The conclusion of this study emphasizes the close relationship between sound structure and meaning in the Qur’an and shows that al-jinās is a stylistic element that is difficult to preserve fully in the translation process. These findings contribute to the development of Qur’an translation studies, particularly in understanding the challenges of transferring rhetorical elements from Arabic into Indonesian.